Pedagogical Innovation in Youth Basketball: a Hard, Urgent Task - Gonçalves, C. E.; Martins, A. M.; Carvalho, H. M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
Research in Sport Pedagogy has opened diverse and innovative teaching approaches both theoretically and practically. However, research findings have had little impact in altering coaches’ behaviours. The present study aims to examine the structure of practices in youth basketball teams and the perceptions of the coaches about pedagogical innovation. Twelve under-16 teams, ranging in ability from local to elite (8 male and 4 female) participated in the study. Each team was video recorded in all weekly practices during the competitive season using the reduced version of CAIS . Twelve coaches (aged 29 to 65 years, with 9 to 35 years of experience), attended semi-structured interviews about their concepts and use of pedagogical innovation. No diversity in practice structure was observed among the 12 coaches/teams. The only factor that influenced the sequence and contents of the sessions was time to competition. Eight of the coaches said they did not care about sport pedagogy theories. The other four were aware of recent theories but, in their opinion, “it does not work”, because competition prevails over active learning. All coaches considered that every game with opposition in practice represents “decision making training”. The findings corroborate previous research suggesting that coaches construct their knowledge embedded in their sport and club culture, and that coach education programmes seem to have little relevance for coaches´ behaviour change.